A microsomal based method to detect aromatase activity in different brain regions of the rat using ultra performance liquid chromatography–mass spectrometry. Issue 163 (October 2016) - Li, Junyi; Oberly, Patrick J.; Poloyac, Samuel M.; Gibbs, Robert B.
Highlights: A microsomal based method was developed to detect aromatase (ARO) activity in different brain regions of the rat using ultra performance liquid chromatography–mass spectrometry. The microsomal incubation assay has been validated with high sensitivity, specificity and reliability. Using this method, we showed a correlation between ARO activity and relative levels of the long form of CYP19A1 mRNA. Abstract: Aromatase (ARO) is a cytochrome P450 enzyme that accounts for local estrogen production in the brain. The goal of this study was to develop a microsomal based assay to sensitively and reliably detect the low levels of ARO activity in different brain regions. Enzyme activity was detected based on the conversion of testosterone to estradiol. Quantity of estradiol was measured using ultra performance liquid chromatography–mass spectrometry. Detection was linear over a range of 2.5–200 pg/ml estradiol, and was reproducible with intra- and inter-assay coefficients of variation (CV) <15%. Estradiol production using isolated microsomes was linear with time up to 30 min as well as linearly related to amount of microsome. Substrate concentration curves revealed enzymatic kinetics (hippocampus: V max and K m : 0.57 pmol estradiol/h per mg microsome and 48.58 nM; amygdala: V max and K m : 1.69 pmol estradiol/h per mg microsome and 48.4 nM; preoptic area: V max and K m : 0.96 pmol estradiol/h per mg microsome and 44.31 nM) with testosterone used at a saturating concentration of 400 nM. Anastrozole treatment blocked ARO activity in hippocampal and ovarian microsomes, indicating that the assay is specific for ARO. Also, we showed that the distribution of the long form ARO mRNA (CYP19A1) in different regions of the brain is correlated with ARO activity, with highest levels in the amygdala, followed by preoptic area and hippocampus. In the frontal cortex, very little long form ARO mRNA, and little to no ARO activity, were detected. These findings demonstrate that the microsomal incubation (MIB) assay is a sensitive and reliable method for quantifying ARO activity in discrete brain regions.